Penguatan Kelembagaan Desa Melalui Peningkatan SDM Aparatur Pemerintahan Desa dan Memasukkan Unsur ASN dalam Pemerintahan Desa - Hoiru Nail, Muhammad (Prodi Ilmu Hukum Fakultas Hukum Universitas Islam Jember, 2022)
Village Government with the promulgation of Law Number 6 of 2014 concerning Villages clearly indicates that there are efforts to strengthen village institutions or the existence of villages is very large and strategic in development and realizing welfare for the people. The initial government units from ministries, provincial and district/city governments in their apparatus are accompanied by the State Civil Apparatus without exception, but it is questionable that in the village government unit there is not a single apparatus from the State civil apparatus. The village government which is a government that is directly related to the people needs to be considered especially for the sake of strengthening and improving services to the community by including elements of the State Civil Apparatus in it.